2016
DOI: 10.1093/gbe/evw166
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into Chromosome Evolution in Birds, Archosaurs, and Reptiles

Abstract: Homologous synteny blocks (HSBs) and evolutionary breakpoint regions (EBRs) in mammalian chromosomes are enriched for distinct DNA features, contributing to distinct phenotypes. To reveal HSB and EBR roles in avian evolution, we performed a sequence-based comparison of 21 avian and 5 outgroup species using recently sequenced genomes across the avian family tree and a newly-developed algorithm. We identified EBRs and HSBs in ancestral bird, archosaurian (bird, crocodile, and dinosaur), and reptile chromosomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 44 publications
4
99
0
Order By: Relevance
“…A total of 69 intrachromosomal EBRs were detected in the falcon lineage (Supplemental Table S8; Supplemental Results). Consistent with our previous report (Farré et al 2016), falcon intrachromosomal EBRs were found highly enriched for the LTR-ERV1 transposable elements (TEs; t-test P < 0.05) (Supplemental Table S9). Both fusion and fission EBRs were not significantly enriched for any type of TEs.…”
Section: Falcon Chromosome Assemblysupporting
confidence: 90%
See 4 more Smart Citations
“…A total of 69 intrachromosomal EBRs were detected in the falcon lineage (Supplemental Table S8; Supplemental Results). Consistent with our previous report (Farré et al 2016), falcon intrachromosomal EBRs were found highly enriched for the LTR-ERV1 transposable elements (TEs; t-test P < 0.05) (Supplemental Table S9). Both fusion and fission EBRs were not significantly enriched for any type of TEs.…”
Section: Falcon Chromosome Assemblysupporting
confidence: 90%
“…Regardless of the mechanism, comparisons of multiple animal genomes show that between EBRs are evolutionary stable homologous synteny blocks (HSBs). Our studies in mammals ) and birds (Farré et al 2016) suggest that at least the largest HSBs are maintained nonrandomly and are highly enriched for conserved noncoding elements (CNEs), many of which are gene regulatory sequences and miRNAs (Zhang et al 2014b). We recently hypothesized that a higher fraction of elements under negative selection involved in gene regulation and chromosome structure in avian genomes (∼7%) (Zhang et al 2014b) compared with mammals (∼4%) (Lindblad-Toh et al 2011) could contribute to some avian-specific phenotypes and the evolutionary stability of most avian karyotypes (Farré et al 2016).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 88%
See 3 more Smart Citations